1996
DOI: 10.1007/bf00017808
|View full text |Cite
|
Sign up to set email alerts
|

Light-modulated abundance of an mRNA encoding a calmodulin-regulated, chromatin-associated NTPase in pea

Abstract: A CDNA encoding a 47 kDa nucleoside triphosphatase (NTPase) that is associated with the chromatin of pea nuclei has been cloned and sequenced. The translated sequence of the cDNA includes several domains predicted by known biochemical properties of the enzyme, including five motifs characteristic of the ATP-binding domain of many proteins, several potential casein kinase II phosphorylation sites, a helix-turn-helix region characteristic of DNA-binding proteins, and a potential calmodulin-binding domain. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 35 publications
(39 reference statements)
3
66
0
Order By: Relevance
“…A search of protein and nucleotide databases using the NCB1 TBLASTN and BLASTN programs (23) showed no significant similarities of LNP to the amino acid or cDNA sequences of any other plant or animal lectin yet described. It did, however, show 65.6% and 47.6% amino acid identity and 70.7% and 58.7% nucleotide identity with the sequences of a pea nucleotide triphosphatase (24) and an apyrase isolated from potato tubers (25), respectively. Considerably less, but significant, similarity also was found with the sequences of several other animal and yeast phosphohydrolases.…”
Section: Resultsmentioning
confidence: 99%
“…A search of protein and nucleotide databases using the NCB1 TBLASTN and BLASTN programs (23) showed no significant similarities of LNP to the amino acid or cDNA sequences of any other plant or animal lectin yet described. It did, however, show 65.6% and 47.6% amino acid identity and 70.7% and 58.7% nucleotide identity with the sequences of a pea nucleotide triphosphatase (24) and an apyrase isolated from potato tubers (25), respectively. Considerably less, but significant, similarity also was found with the sequences of several other animal and yeast phosphohydrolases.…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme requires activation by Ca 2ϩ -bound calmodulin to convert Glu to ␥-aminobutyric acid, which is rapidly accumulated in nodules in response to various stresses (Ling et al, 1994;Serraj et al, 1998). Apyrase, another enzyme known for its calmodulin-binding properties (Hsieh et al, 1996), has also been reported to play an essential role in plant-rhizobium symbiosis (Cohn et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The NH 2 -terminal 445-amino acid hydrophilic segment of Apy1p contains the apyrase domain. The apyrase domains of other E-ATPases are all located extracellularly, through either a cleaved (6,8,9) or a noncleaved signal sequence (5,14,17). Surprisingly, there is no signal sequence in the NH 2 -terminal portion of Apy1p; in addition, this domain (445 amino acids) is much larger than the extracellular domain of known type III membrane proteins (Ͻ100 amino acids) (51).…”
Section: Cloning Of the Apy1 Gene From Yeast Chromosomal Dna-mentioning
confidence: 99%
“…The molecular identity of the E-ATPases was revealed recently by the purification and cloning of a soluble apyrase from potato tubers (Solanum tuberosum) (6). The deduced amino acid sequence for potato apyrase had sequence similarities with various other polypeptides in the data base, including CD39, a human and mouse lymphoid cell antigen (7), garden pea NTPase (8), and Toxoplasma gondii NTPase (9). All of these proteins contain four highly conserved sequences called apyrase conserved regions (ACR1-4).…”
mentioning
confidence: 99%